Pinjaman Online Ilegal, Dana Cepat Ujungnya Tersesat - Aguk Nugroho; Vivin Astharyna Harysart; Armaya Mangkunegara; Marwan Marwan; Achmad Wildan Dimyati; Ciptono Ciptono; Dhyan Purwitarini (Pusat Riset dan Inovasi Nasional, 2026)
The rapid development of information technology has increased the use of online lending services, including illegal platforms that impose excessive interest rates, misuse personal data, and employ intimidating debt collection practices. Limited legal and digital literacy has made communities more vulnerable to these risks. This Community Service Program aims to enhance the understanding of residents in Kradenan Village, Tuban Regency regarding the characteristics of illegal online loans, their social, economic, and psychological impacts, and the relevant legal protections under regulations such as the Electronic Information and Transactions Law, the Personal Data Protection Law, and OJK Regulation No. 77/2016. Through participatory legal education and interactive discussions, the program achieved full participation and improved participants’ knowledge by up to 75%. Residents became more capable of identifying illegal loan applications, recognizing data misuse risks, and understanding preventive measures and available legal remedies. This program effectively increased public awareness to use digital financial services more responsibly and avoid the dangers of illegal online lending.